THE USE OF AUTHENTIC MATERIALS IN EFL/ESL CLASSROOM - Loli Safitri (English Study Program University of Pasir Pengaraian, 2017)
Teaching material is one of crucial part in English Foreign Language (EFL) classroom. Teaching language is related to the teaching culture which has great influence in human life. One better way to introduce students to the real world is through the use of authentic material. Since EFL students get more difficulties in acquire and explore the language, it can help them to experience real-world events in the classroom. Using authentic material enables teacher to modify teaching and learning strategies into a collaborative and interactive student centered learning environment instead of traditional teacher centered. Audio and visual presentation of the authentic material makes teaching and learning condition more interesting. Based on the previous explanation, this paper is focused on the use of authentic material in teaching and learning English in EFL classroom. It also describes how authentic material helps students improve their language skills and motivate them to learn English.